Rare bird documentation form for Greater Scaup at Coralville Reservoir, 1976 - Halmi, Nicholas S.et al (1976)
Rare bird documentation form for a Greater Scaup at Coralville Reservoir in Johnson County, IA on March 20, 1976. Epson - sheet feed